Discharge education to promote self-management following cardiovascular surgery: An integrative review. (1st February 2014) - Veronovici, Nicole R; Lasiuk, Geraldine C; Rempel, Gwendolyn R; Norris, Colleen M
Abstract: Background: Nurses have a key role in teaching cardiovascular (CV) surgical patients to manage their post-surgical care after discharge. There is evidence that effective patient teaching contributes to improved quality of life, decreased anxiety and depression and fewer post-CV surgery emergency department visits and hospital readmissions. Despite this, there are no guidelines or standards for how best to educate CV surgical patients for discharge. Aim: To conduct a literature review of published research on discharge education for CV surgical patients to inform guidelines for educating CV surgical patients. Method: An exhaustive search of CINAHL, Medline, Web of Science, Cochrane Database of Systematic Reviews, and ERIC was executed using the following search terms: cardiovascular, cardiac, cardio*, heart, surg*, transplant, discharge, self-manage*, teach*, educat*, preop*, patient, care. In addition, an ancestry search of all reference lists was completed. Studies were included if they were published between 2007 and 2012 and focused on preoperative CV surgery adult patient education. Results: The search yielded 20 studies, 12 were excluded because they did not meet the inclusion/exclusion criteria. Eight studies were included in the final review. Three studies reported statistically significant decreases in reported anxiety and depression and increased subjective health. Four studies had mixed results with both positive and neutral findings. No studies reported negative findings in relation to preoperative education. Conclusion: Patients and staff identified that patient education is essential. Standardized educational tools are appropriate as they can spare resources, but are only effective if used in conjunction with individualized education.